Heuristics and Bias in Indonesian Elections: The Effect of Gender and Academic Degrees on Voter Preference - Sekar Ayu; Aira Jasmine Nabilla Alfianti; Clarisa Arfiandani (Mengeja Indonesia Publisher, 2021)
In the general election for legislative candidates, which is attended by dozens of candidates in one electoral district, often voters do not have sufficient information about the background and performance of the competing candidates. This study explores how a voter chooses his deputy candidate with inadequate information on the candidates. In conditions of low candidate personal information, voters use various attributes or any clues listed on the ballot to help them make decisions in a limited time. In political psychology, mental processes like this are referred to as heuristics. Using an online experimental method and a 2x2 factorial design as well as a two-way ANOVA statistical test, this study examines two forms of heuristics that voters might use to help make political decisions, namely gender and academic degrees. This study indicates that neither gender nor academic degree has a significant effect on encouraging voters to choose. This is evidenced by the results of experimental research studies, which show that each variable has a significance greater than 0.05.